2006
DOI: 10.1080/14017430500338513
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension. Ten years experience in Denmark

Abstract: Pulmonary endarterectomy has been successfully implemented in Denmark. The perioperative mortality was reduced over time to 9% during the past 5 years. Functional outcome and long-term survival were excellent stressing the importance of surgical treatment for chronic thromboembolic pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients. There was one retrospective study from Austria that compared hemodynamic indices between PTE and non-PTE patients with a 1-year follow-up, but could not be included in the current review due to insufficient data to meet the inclusion criteria.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients. There was one retrospective study from Austria that compared hemodynamic indices between PTE and non-PTE patients with a 1-year follow-up, but could not be included in the current review due to insufficient data to meet the inclusion criteria.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Only the most recent publications with the most complete data set from each institute were retained. As a result, 19 studies 6,15,21,22,25,26,29,30,33,35,36,38,40,[42][43][44][46][47][48] with a total number of 2729 patients were included for appraisal and data extraction ( Table 2).…”
Section: Quantity Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In-hospital mortality rates for patients who have undergone PEA range from 5% to 24% [5,10,11], and in general, periprocedural mortality rates of 5-11% are achieved [1,9,12]. However, not all patients are eligible for surgery because of an inaccessible and/or distal thromboembolism, or serious comorbidities [13,14].…”
mentioning
confidence: 99%
“…However, not all patients are eligible for surgery because of an inaccessible and/or distal thromboembolism, or serious comorbidities [13,14]. Moreover, PH can persist or reappear in patients who have undergone PEA, and persistent PH is one of the most important determinants of post-PEA outcome [11,15,16]. Furthermore, high mean pulmonary arterial pressure (Ppa) is an independent predictor of death in patients with ''chronic PE'' (p50.04) [17].…”
mentioning
confidence: 99%